2009
DOI: 10.1055/s-0028-1109882
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable Cerebrospinal Fluid Shunt Valves in 3.0-Tesla MRI: a Phantom Study using Explanted Devices

Abstract: Until suggestions can be made concerning the exposure of hydrocephalic patients to 3.0 T-MRI, further testing is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 22 publications
1
12
0
1
Order By: Relevance
“…There have been conflicting reports regarding the tolerance of these valves to exposure to a 3T magnetic field;[138] however, we found that even multiple exposures to a 3T magnetic field (consistent with six complete MRI scans in one day) has no detrimental effect on the programming mechanisms.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…There have been conflicting reports regarding the tolerance of these valves to exposure to a 3T magnetic field;[138] however, we found that even multiple exposures to a 3T magnetic field (consistent with six complete MRI scans in one day) has no detrimental effect on the programming mechanisms.…”
Section: Discussionsupporting
confidence: 51%
“…Similar results have been reported by other investigators, and emphasize the importance of evaluating patients as soon as possible after an MRI scan to avoid problems from over- or underdrainage of CSF. [139] When MR imaging is being performed on an emergency basis in a patient with a CSF shunt (e.g. presentation with acute stroke symptoms), it is highly recommended that pre- and postimaging X-rays of the shunt-valve be obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several magnetically programmable CSF shunt valves have been evaluated in association with MRI [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The 3-T MRI environment has been reported to pose problems that do not exist at 1.5 T. The difference is likely due to the nature of the mechanism of action involved in the magnetic components of a given shunt valve relative to this powerful static magnetic field [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
mentioning
confidence: 99%
“…B. der Magnete spürbar. Deshalb sollte bei MRT-Untersuchungen auch eine nur geringfügige Verminderung der Magnetkraft vermieden werden.Neben den viel untersuchten Wechselwirkungen zwischen starken MRT-Feldern und inkorporierten, medizinisch genutzten Permanentmagneten wie Erhitzung, Beschleunigung und Artefaktbildung wird der möglichen Demagnetisierung auch in neuesten Studien weniger Aufmerksamkeit geschenkt[12], obwohl die jeweiligen Vorrichtungen durch Änderungen des Magnetfeldes insuffizient werden können. Um die Dentalmagnete MRT-fest zu machen, müssten die Hersteller Legierungen mit maximaler Koerzitivfeldstärke benutzen; nach heutigem Technikstand würden sie damit in den derzeit am weitesten verbreiteten 1,5 T-MRT stabil bleiben.…”
unclassified